Mutation at the TrkB PLCγ-docking site affects hippocampal LTP and associative learning in conscious mice - Gruart, A; Sciarretta, C; Valenzuela-Harrington, M; Delgado-García, JM; Minichiello, L (Cold Spring Harbor Laboratory Press, 2007)
Previous in vitro studies have characterized the electrophysiological properties and molecular events associated with long-term potentiation (LTP), but as yet there are no in vivo data from molecular-level dissection that directly identify LTP as the biological substrate for learning and memory. Understanding whether the molecular pathways required for learning are also those generating LTP when measured directly on the relevant circuit of a learning animal is clearly important, although so far has proved technically difficult. Here, for the first time, we combine highly defined genetic mouse models with behavior and in vivo recordings. We recorded the activity-dependent changes taking place at the CA3–CA1 synapses during the acquisition and extinction of a simple form of an associative learning task in mice carrying point mutations on specific docking sites of TrkB receptors (trkBSHC, trkBPLC). The learning task consisted of a classical eyeblink conditioning using a trace paradigm. The conditioned stimulus (CS) consisted of a tone and was followed by a periorbital electrical shock as an unconditioned stimulus (US). The US started 500 msec after the end of the CS. We show that a single pulse presented to the Schaffer collateral-commissural pathway during the CS-US interval evoked a monosynaptic field excitatory postsynaptic potential (fEPSP) at the CA1 pyramidal cells, with a slope linearly related to learning evolution in controls and trkBSHC mutants, but the relationship was impaired in trkBPLC mice. These data support a link between the PLCγ-docking site downstream of TrkB and the activity-dependent synaptic changes evoked at the CA3–CA1 synapses during associative learning in conscious mice, and indicate that TrkB PLCγ-site-activated molecular pathway(s) underlie both associative learning and LTP triggered at the CA3–CA1 synapse.